The Complex Interactions Between Flowering Behavior and Fiber Quality in Hemp - Salentijn, Elma M. J.; Petit, Jordi; Trindade, Luisa M. (Frontiers in Plant Science, 2019)
Hemp, Cannabis sativa L., is a sustainable multipurpose fibre crop with high nutrient and water use efficiency and with biomass of excellent quality for textile fibres and construction materials. The yield and quality of hemp biomass are largely determined by the genetic background of the hemp cultivar but are also strongly affected by environmental factors, such as temperature and photoperiod. Hemp is a facultative short-day plant, characterized by a strong adaptation to photoperiod and a great influence of environmental factors on important agronomic traits such as “flowering-time” and “sex determination”. This sensitivity of hemp can cause a considerable degree of heterogeneity, leading to unforeseen yield reductions. Fibre quality for instance is influenced by the developmental stage of hemp at harvest. Also, male and female plants are differing in stature and produce fibres with different properties and quality. Next to these causes, there is evidence for specific genotypic variation in fibre quality among hemp accessions. Before improved hemp cultivars can be developed, with specific flowering-times and fibre qualities, and adapted to different geographical regions, a better understanding of the molecular mechanisms controlling important phenological traits such as “flowering-time” and “sex determination” in relation to fibre quality in hemp is required. It is well known that genetic factors play a major role in the outcome of both phenological traits but, the major molecular factors involved in this mechanism are not characterized in hemp. Genome sequences and transcriptome data are available but their analysis mainly focussed on the cannabinoid pathway for medical purposes. Herein, we review the current knowledge of phenotypic- and genetic data available for “flowering-time”, “sex determination” and “fibre quality” in short-day and dioecious crops, respectively, and compare them with the situation in hemp. A picture emerges for several controlling key genes, for which natural genetic variation may lead to desired flowering behaviour, including examples of pleiotropic effects on yield quality and on carbon partitioning. Finally we discuss the prospects for using this knowledge for the molecular breeding of this sustainable crop via a candidate gene approach.